2020
DOI: 10.1186/s12905-019-0867-2
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal, infant, and child mortality among women exposed to intimate partner violence in East Africa: a multi-country analysis

Abstract: Background: Most neonatal, infant, and child deaths occur in low-and middle-income countries (LMICs), where incidence of intimate partner violence (IPV) is highest in the world. Despite these facts, research regarding whether the two are associated is limited. The main objective was to examine associations between IPV amongst East African women and risk of death among their neonates, infants, and children, as well as related variables. Methods: Analysis was conducted on data drawn from the Demographic and Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 17 publications
4
33
2
8
Order By: Relevance
“…Under-five mortality in this study is a binary variable and is considered to be present if the index child died before reaching the fifth birthday within five years before the mother's interview (coded as 1), and absent if the index child was alive at the time of mother's interview (coded as 0). Many studies have similarly constructed the outcome child mortality variable using Demographic and Health Surveys data [19][20][21][22]. The age distribution of the underfive children in our sample is given in Figure 1.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Under-five mortality in this study is a binary variable and is considered to be present if the index child died before reaching the fifth birthday within five years before the mother's interview (coded as 1), and absent if the index child was alive at the time of mother's interview (coded as 0). Many studies have similarly constructed the outcome child mortality variable using Demographic and Health Surveys data [19][20][21][22]. The age distribution of the underfive children in our sample is given in Figure 1.…”
Section: Study Outcomesmentioning
confidence: 99%
“…If the index child died before reaching the fifth birthday within five years before the mother's interview (coded as 1), and absent if the index child was alive at the time of mother's interview (coded as 0). Many studies have similarly constructed the outcome child mortality variable using Demographic and Health Surveys data [19][20][21][22]…”
Section: Study Outcomesmentioning
confidence: 99%
“…A range of proximal (e.g., health-related factors), intermediate (e.g., water and sanitation), and distal (e.g., education and income) determinants are thought to predict infant and child mortality (Mosley & Chen, 2003). These determinants include breastfeeding (Iram & Butt, 2008;Lamichhane et al, 2017;Reno & Hyder, 2018), baby's birth size and weight (Lamichhane et al, 2017;Memiah et al, 2020;Vidal e Silva et al, 2018), and place and type of delivery (Iram & Butt, 2008;Lamichhane et al, 2017;Memiah et al, 2020). Poor health of newborn (Vidal e Silva et al, 2018), prenatal and postnatal care (Iram & Butt, 2008;Reno & Hyder, 2018), multiple births (Dwomoh et al, 2019;Vidal e Silva et al, 2018), and birth interval (Dwomoh et al, 2019;Lamichhane et al, 2017;Reno & Hyder, 2018) are also found to be associated with infant mortality.…”
Section: Introductionmentioning
confidence: 99%